Implementation of borrow-used evidence criminal case in Makassar City - Suhadi Suhadi; Syamsuddin Muchtar; Audyna Mayasari Muin (The International Journal of Politics and Sociology Research, 2023)
This research examined the legal framework for borrowing and exploiting evidence in criminal trials in Makassar City and the legal protections for evidence owners. Research is empirical normative legal. The investigation found that (1) the lending and use of evidence is governed by unique norms at each level of examination, not by law. (2) The form of legal protection for the owner of evidence in borrowing and using evidence is preventive legal protection, law enforcement does not immediately give permission because it is feared that it will disappear or change form, granting permission by looking at whether the loan is appropriate or not based on the level of urgency, and fulfilling the formal requirements which refers to Article 44 paragraph (2) of Law 8/1981 concerning the Criminal Procedure Code jo. Article 30 PP 27/1983 concerning the Implementation of the Criminal Procedure Code, as well as material requirements referring to the rules for each level of examination, and repressive legal protection, Article 46 of the Criminal Procedure Code, to minimize disputes in Article 221 paragraph (1) number (2) and Article 233 Law 1/1946 concerning Criminal Law Regulations, Article 10 paragraph (2) letter (h) Perpol 7/2022 concerning the Professional Code of Ethics and the Police Code of Ethics Commission, Article 7 paragraph (1) letter (f) and (h) Perja-RI No.PER- 014/A/JA/11/2012 Concerning the Prosecutor's Code of Conduct and to avoid disputes most of the evidence is returned after an inkracht decision from the Court. The implication of this research is to be able to analyze the legal framework and policies governing the use of loan-to-use evidence in the criminal justice system in Makassar. In this regard, it is important to understand whether the existing legal and policy framework is sufficiently clear and consistent to facilitate the effective use of proof of use, and whether there is a need to update or improve existing regulations.